Close Encounters for the First Time: Helicase Interactions with DNA Damage - Khan, Irfan (DNA Repair (Amst), 2015)
DNA helicases are molecular motors that harness the energy of nucleoside triphosphate hydrolysis to unwinding structured DNA molecules that must be resolved during cellular replication, DNA repair, recombination, and transcription. In vivo, DNA helicases are expected to encounter a wide spectrum of covalent DNA modifications to the sugar phosphate backbone or the nitrogenous bases; these modifications can be induced by endogenous biochemical processes or exposure to environmental agents. The frequency of lesion abundance can vary depending on the lesion type. Certain adducts such as oxidative base modifications can be quite numerous, and their effects can be helix-distorting or subtle perturbations to DNA structure. Helicase encounters with specific DNA lesions and more novel forms of DNA damage will be discussed. We will also review the battery of assays that have been used to characterize helicase-catalyzed unwinding of damaged DNA substrates. Characterization of the effects of specific DNA adducts on unwinding by various DNA repair and replication helicases has proven to be insightful for understanding mechanistic and biological aspects of helicase function in cellular DNA metabolism.